Adding or destroying value? User experiences of tourism self-service technologies. Issue 3 (31st May 2019) - Kelly, Petranka; Lawlor, Jennifer
Abstract : Purpose: The global tourism industry is continuing to experience a change from high-touch to high-tech with the increasing implementation of self-service technologies (SSTs) such as hotel reservation websites, kiosk technologies at airports and smartphone applications. SSTs require active customer involvement in the service delivery process and as such, the customer serves as a co-creator of value along with the tourism provider. Although there are benefits to customer involvement in service provision, there is a risk that SST usage may also detract value from the service experience. Therefore, the purpose of this paper is to explore customer perspectives on their experiences of SST usage in a tourism context, through the theoretical lens of the service–dominant logic framework. Design/methodology/approach: This interpretivist study employs a two-stage qualitative methodology of short interviews with 133 participants at an international airport, followed by 32 in-depth interviews with SST users in a tourism context. Findings: Six diverse customer SST experiences are identified and then classified in terms of being either value-creating or value-destroying. The first two experiences accruing from SST usage, namely accomplishment and supportiveness, are deemed to be value-creating, while the experiences of lack of control, manipulation, concern about discrimination and social tension are deemed to be value-destroying. Originality/value: The study responds to a gap in the literature regarding the concept and nature of customer value co-creation pertaining to the use of SSTs in a tourism context. The research findings indicate that value is not only created but may also be destroyed in the SST encounter. The study also illustrates that SST usage may have a strong social element in terms of the presence and role of other customers and employees. This challenges the consensus in the literature that SST usage reduces or removes human interaction.